Strong-adhesion high-stretchability self-healing hydrogel capable of being rapidly formed and preparation method thereof
By combining aminophenylboronic acid-modified glycyrrhizic acid molecules with polyvinyl alcohol skeleton materials, a self-healing hydrogel with rapid molding, strong adhesion, and high stretchability was prepared, which solved the problems of insufficient mechanical and adhesion properties of existing hydrogels, adapted to the specific needs of different wound environments, and achieved rapid self-healing and biosafety.
Patent Information
- Application Number
- CN202511128797.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-08-13
AI Technical Summary
Existing self-healing hydrogels have deficiencies in mechanical properties, adhesion properties and stretchability, making it difficult to meet the specific needs of different wound environments.
Glycyrrhizic acid molecules were modified with aminophenylboronic acid and introduced into the hydrogel system through dynamic borate bonds. Polyvinyl alcohol with excellent biocompatibility was used as the skeleton material, and the phenylboronic acid group and hydroxyl group were combined as the main force to achieve rapid molding and high stretchability.
The prepared hydrogel has rapid molding ability, strong adhesion and high tensile properties, can be quickly reconstructed after physical damage, adapt to the specific needs of different wound environments, and ensure biosafety and stable fit.
Smart Images

Figure CN120623516A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogel materials, and in particular to a rapidly moldable, strongly adhesive, highly stretchable, self-healing hydrogel and a preparation method thereof. Background Art
[0002] Self-healing hydrogels have become a research hotspot due to their excellent biocompatibility and structural recoverability under external forces, and their ability to dynamically adapt to complex wound microenvironments.
[0003] Glycyrrhizic acid (GA), a natural triterpenoid saponin, exhibits significant anti-inflammatory, antibacterial and antiviral activities and has great potential in promoting wound healing.
[0004] Currently, the use of glycyrrhizic acid can be roughly divided into the following two categories: one is to take advantage of the unique molecular structure of glycyrrhizic acid, adding metal ions to achieve self-assembly of glycyrrhizic acid molecules, or using temperature to regulate its self-assembly behavior, and using glycyrrhizic acid as a hydrogel backbone. The other is to mainly exert its drug activity, adding it to the hydrogel network, while also utilizing glycyrrhizic acid's structural characteristics to assist in hydrogel formation.
[0005] Patent publication number CN110585122A discloses an injectable antibacterial hydrogel based on natural triterpenoid compounds and its preparation method. The hydrogel disclosed in this invention utilizes a mixture of glycyrrhizic acid and either a pentacyclic or tetracyclic triterpenoid compound as the gelling molecules, using phosphate-buffered saline (PBS) as the gelling solvent. The hydrogel is prepared through a small molecule self-assembly mechanism, utilizing the non-covalent bonds formed between the mixture. However, the mechanical properties of the hydrogel obtained solely by relying on non-covalent bonds between small molecules are poor.
[0006] Dynamic covalent bonds, particularly borate ester bonds, have been widely introduced into self-healing hydrogels due to their reversibility and pH responsiveness. However, existing borate ester hydrogels generally suffer from significant limitations: insufficient self-healing properties and low modulus, as well as weak adhesion and stretchability, making them difficult to meet the mechanical and interfacial integration requirements of specific wound dressings for diverse wound environments.
[0007] In view of this, it is necessary to design a rapidly formed, strongly adhesive, highly stretchable self-healing hydrogel and its preparation method to solve the above problems. Summary of the Invention
[0008] The present invention aims to provide a rapidly moldable, strongly adhesive, and highly stretchable self-healing hydrogel and its preparation method. This preparation method uses aminophenylboronic acid to modify glycyrrhizic acid, using the modified glycyrrhizic acid molecules as key cross-linking units or functional components, innovatively and efficiently introducing dynamic borate ester bonds into the hydrogel system.
[0009] This application achieves wide-range, controllable regulation of the hydrogel modulus by precisely controlling the reaction conditions. The unique molecular structure of glycyrrhizic acid and the large number of hydroxyl groups in the system give it excellent adhesion to different substrates. At the same time, due to the presence of borate bonds, its ability to rapidly rebuild gives the hydrogel good self-healing and tensile properties. This application uses biocompatible and degradable polyvinyl alcohol (PVA) as the main skeleton material for the hydrogel to ensure the overall biosafety of the material.
[0010] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a rapidly molded, strongly adhesive, and highly stretchable self-healing hydrogel, comprising the following steps: S1, preparation of carboxylated methacryloyl polyvinyl alcohol: polyvinyl alcohol is completely dissolved in a reaction vessel containing an organic solvent, followed by addition of a catalyst; thereafter, a glycidyl methacrylate solution is added, reacted for 5-10 hours, and then a succinic anhydride solution is added, and the reaction is continued for 5-10 hours. After completion of the reaction, the pH of the reaction solution is adjusted to 7-9; the solution is then precipitated with acetone, filtered, and dialyzed for 48-72 hours. Finally, the dialyzate is frozen and freeze-dried to obtain the carboxylated methacryloyl polyvinyl alcohol; S2, preparation of dipotassium glycyrrhizinate with phenylboronate: dipotassium glycyrrhizinate is completely dissolved in dimethyl sulfoxide, followed by addition of N-hydroxysuccinimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and 3-aminophenylboronic acid, and the mixture is reacted at 25-35°C for 20-48 hours; the reaction solution is then dialyzed for 48-72 hours, and the dialyzate is filtered and freeze-dried to obtain dipotassium glycyrrhizinate with phenylboronate; S3, the carboxylated methacryloyl polyvinyl alcohol prepared in step S1 is prepared into a solution A with a concentration of 10% to 12%, and the phenylborated dipotassium glycyrrhizate prepared in step S2 is prepared into a solution B with a concentration of 6% to 10%, and solution A and solution B are extruded and blended through a double-barreled syringe to obtain a self-healing hydrogel with strong adhesion and high stretchability that can be rapidly formed.
[0011] As a further improvement of the present invention, in step S1, the mass ratio of the polyvinyl alcohol to glycidyl methacrylate is 1:(0.064-0.1).
[0012] As a further improvement of the present invention, when the mass ratio of the polyvinyl alcohol to glycidyl methacrylate is 1:(0.064-0.0652), the degree of substitution of the double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.007-0.01; when the mass ratio of the polyvinyl alcohol to glycidyl methacrylate is 1:(0.096-0.1), the degree of substitution of the double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.018-0.021.
[0013] As a further improvement of the present invention, in step S2, the molar ratio of the carboxyl group on dipotassium glycyrrhizate to the amino group on 3-aminophenylboronic acid is 3:(1.25-1.3).
[0014] As a further improvement of the present invention, in step S1, the mass ratio of succinic anhydride to polyvinyl alcohol is (1-4):10.
[0015] As a further improvement of the present invention, in step S1, the organic solvent is one of dimethyl sulfoxide, DMF, and chloroform.
[0016] As a further improvement of the present invention, in step S1, the catalyst is p-dimethylaminopyridine, and the mass ratio of p-dimethylaminopyridine to polyvinyl alcohol is (0.1-0.15):5.
[0017] As a further improvement of the present invention, in step S1, the pH of the solution is adjusted by dropwise adding a sodium bicarbonate solution to the reaction system.
[0018] The present invention also provides a rapidly moldable, strongly adhesive, and highly stretchable self-healing hydrogel. The rapidly moldable, strongly adhesive, and highly stretchable self-healing hydrogel has an adhesion strength of 20 to 65 kPa and a tensile strain of 300 to 1050%.
[0019] The beneficial effects of the present invention are: 1. The present invention provides a method for preparing a rapidly moldable, strongly adhesive, and highly stretchable self-healing hydrogel. This method utilizes crosslinking of phenylboronic acid groups with hydroxyl groups and double bonds as the primary force, with hydrophilic and hydrophobic interactions (glycyrrhizic acid is composed of one molecule of hydrophobic glycyrrhetinic acid and two molecules of hydrophilic glucuronic acid) acting as a secondary force. This method significantly shortens gelation time and improves the hydrogel's mechanical properties. Specifically, glycyrrhizic acid is modified with aminophenylboronic acid, and dynamic boronate bonds impart rapid and efficient self-healing capabilities to the hydrogel. After physical damage or cutting, the hydrogel structure rapidly rebuilds and restores its integrity, extending its service life while maintaining its barrier and functional properties. This method significantly outperforms existing glycyrrhizic acid or borate ester hydrogels, which have poor self-healing properties and slow recovery.
[0020] 2. By precisely controlling the degree of double bond substitution of modified polyvinyl alcohol, the present invention achieves wide and controllable adjustment of the hydrogel modulus. This property enables the hydrogel produced by the present invention to flexibly adapt to the specific mechanical properties (softness and hardness) requirements of wound dressings in different locations (such as active and static areas of joints) and at different depths, overcoming the limitations of existing hydrogel technologies, which often have a single or uncontrollable modulus.
[0021] 3. The hydrogel produced by this invention is rich in hydroxyl groups, which impart strong, long-lasting adhesion to a variety of biological tissues and surfaces. This effectively addresses the critical issue of weak adhesion in existing glycyrrhizic acid composite hydrogels, ensuring stable adhesion of the dressing to the wound and preventing it from falling off.
[0022] 4. The hydrogel of the present invention uses biocompatible and degradable polyvinyl alcohol (PVA) as its main skeleton material. The system does not introduce harmful components, ensuring that the overall material is safe and harmless to the human body and meets the biosafety requirements of wound dressings.
[0023] 5. The present invention uses a double-tube injection method for mixing, which is simple to operate and the solution is mixed evenly. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the synthesis process of carboxylated methacrylylated polyvinyl alcohol in the present invention.
[0025] Figure 2 Schematic diagram of the synthesis process of dipotassium glycyrrhizinate phenylborated in the present invention.
[0026] Figure 3 These are the NMR images of 3-aminophenylboronic acid (B), dipotassium glycyrrhizate (G), and dipotassium glycyrrhizinate phenylboronated (GB) in Example 1 of the present invention.
[0027] Figure 4 This is a diagram of the hydrogel self-healing process of Example 1.
[0028] Figure 5 This is a test diagram of the tensile properties of the hydrogel in Example 1.
[0029] Figure 6 This is a test diagram of the adhesion performance of the hydrogel in Example 1.
[0030] Figure 7 Graph showing the rheological properties-gel time of the hydrogels of Examples 1-3, 5 and Comparative Example 1.
[0031] Figure 8 2. The rheological properties-shear thinning diagram of the hydrogels of Examples 1-3, 5 and Comparative Example 1.
[0032] Figure 9 2. The rheological properties-oscillation strain diagram of the hydrogels of Examples 1-3, 5 and Comparative Example 1.
[0033] Figure 10 Graph showing the rheological properties of the hydrogels of Examples 1-3, 5 and Comparative Example 1, showing the alternating strain diagram.
[0034] Figure 11 Graphs showing the adhesion energy of the hydrogels of Examples 1-2 and 4-5.
[0035] Figure 12 Graph showing the adhesion strength of the hydrogels of Examples 1-2 and 4-5.
[0036] Figure 13 This is a compression performance diagram of the hydrogels of Examples 1-2 and Example 5. DETAILED DESCRIPTION
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] It should also be noted here that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the solutions of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0039] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0040] Hydrogels in existing technologies generally have significant limitations: insufficient self-healing properties and low modulus; or weak adhesion and stretchability, which make it difficult to meet the mechanical properties and interface integration requirements of specific wound dressings required for different wound environments.
[0041] For example, some wounds require strong adhesion, while others do not. Diabetic wounds, for example, require medication and must be biodegradable to prevent secondary damage during dressing changes. Furthermore, gels with too high a modulus can create gaps when in contact with the wound, preventing a good fit and hindering wound repair.
[0042] By precisely controlling the degree of double bond substitution of modified polyvinyl alcohol, the present invention achieves wide-range, controllable adjustment of the hydrogel modulus. This property enables the hydrogel produced by the present invention to flexibly adapt to the specific mechanical properties (softness and hardness) requirements of wound dressings in different locations (such as active and static areas of joints) and at varying depths, overcoming the limitations of existing hydrogel technologies, which often exhibit a single or uncontrollable modulus.
[0043] The present invention provides a method for preparing a rapidly formed, strongly adhesive, and highly stretchable self-healing hydrogel, comprising the following steps: S1, preparation of carboxylated methacryloyl polyvinyl alcohol: polyvinyl alcohol is completely dissolved in a reaction vessel containing an organic solvent, followed by addition of a catalyst; thereafter, a glycidyl methacrylate solution is added, reacted for 5-10 hours, and then a succinic anhydride solution is added, reacted for another 5-10 hours. After completion of the reaction, the pH of the solution is adjusted to 7-9; the solution is then precipitated with acetone, filtered, and dialyzed for 48-72 hours. Finally, the dialyzate is frozen and freeze-dried to obtain the carboxylated methacryloyl polyvinyl alcohol; The mass ratio of polyvinyl alcohol to glycidyl methacrylate is 1:(0.064-0.1).
[0044] When the mass ratio of polyvinyl alcohol to glycidyl methacrylate is 1:(0.064-0.0652), the degree of substitution of the double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.007-0.01.
[0045] When the mass ratio of polyvinyl alcohol to glycidyl methacrylate is 1:(0.096-0.1), the degree of substitution of double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.018-0.021.
[0046] The mass ratio of succinic anhydride to polyvinyl alcohol is (1~4):10.
[0047] The organic solvent is one of dimethyl sulfoxide, DMF and chloroform.
[0048] The solvents of the glycidyl methacrylate solution and the succinic anhydride solution are both organic solvents.
[0049] The catalyst is p-dimethylaminopyridine, and the mass ratio of p-dimethylaminopyridine to polyvinyl alcohol is (0.1-0.15):5.
[0050] The pH of the solution is adjusted by dropwise adding sodium bicarbonate solution to the reaction system.
[0051] S2, preparation of dipotassium glycyrrhizinate with phenylboronate: dipotassium glycyrrhizinate is completely dissolved in dimethyl sulfoxide, followed by addition of N-hydroxysuccinimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and 3-aminophenylboronic acid, and the mixture is reacted at 25-35°C for 20-48 hours; the reaction solution is then dialyzed for 48-72 hours, and the dialyzate is filtered and freeze-dried to obtain dipotassium glycyrrhizinate with phenylboronate; The molar ratio of the carboxyl group on dipotassium glycyrrhizate to the amino group on 3-aminophenylboronic acid is 3:(1.25~1.3).
[0052] S3, the carboxylated methacryloyl polyvinyl alcohol prepared in step S1 is prepared into a solution A with a concentration of 10% to 12%, and the phenylborated glycyrrhizic acid prepared in step S2 is prepared into a solution B with a concentration of 6% to 10%, and solution A and solution B are extruded and blended through a double-barreled syringe to obtain a self-healing hydrogel with strong adhesion and high stretchability that can be rapidly formed.
[0053] The rapidly moldable, strongly adhesive, and highly stretchable self-healing hydrogel prepared by the aforementioned method has an adhesion strength of 20 to 65 kPa and a tensile strain of 300 to 1050%. It can adhere well to different substrates, including glass, plastic, rubber, paper boxes, and weights.
[0054] The following describes the preparation method of the self-healing hydrogel with strong adhesion and high stretchability that can be rapidly formed provided by the present invention in conjunction with specific examples. Unless otherwise specified, the raw materials and reagents in the examples of this application were purchased through commercial channels.
[0055] Experimental example Preparation of dipotassium glycyrrhizinate phenylboronate: Dissolve 4g of dipotassium glycyrrhizate completely in 200ml of dimethyl sulfoxide (DMSO). Add N-hydroxysuccinimide (NHS), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and 3-aminophenylboronic acid. Incubate at 30°C for 24 hours. Dialyze the reaction mixture for 72 hours. Filter the dialyzate and freeze-dry it.
[0056] The molar ratio of carboxyl groups on dipotassium glycyrrhizate to amino groups on 3-aminophenylboronic acid was varied. Specifically, the amount of 3-aminophenylboronic acid was varied and the gel state was observed to determine the molar ratio. It should be noted that the amounts of NHS and EDC were adjusted along with the amount of 3-aminophenylboronic acid, ensuring a ratio of NHS:EDC:amino groups of 1.2:1.2:1.
[0057] The specific molar ratios and experimental results are shown in Table 1.
[0058] Table 1 As shown in Table 1, the molar ratio of the carboxyl group on dipotassium glycyrrhizate to the amino group on 3-aminophenylboronic acid should be determined to be 3:(1.25~1.3).
[0059] Example 1 This embodiment provides a method for preparing a self-healing hydrogel with strong adhesion and high stretchability that can be rapidly formed, comprising the following steps: S1, Preparation of carboxylated methacryloyl polyvinyl alcohol (PGC): 5 g of polyvinyl alcohol (PVA) was weighed and placed in a 250 ml three-necked flask. 90 ml of dimethyl sulfoxide (DMSO) was added and stirred at 40°C until completely dissolved. Subsequently, 0.11 g of catalyst (p-dimethylaminopyridine) was added.
[0060] 0.326 g of glycidyl methacrylate (GMA) was weighed and dissolved in 10 ml of DMSO, and then added to a three-necked flask for reaction for 6 hours. Then, 0.5 g of succinic anhydride (SAA) was weighed and dissolved in 10 ml of DMSO and added to the reaction system. The reaction was continued for 6 hours to terminate the reaction. Then, the resulting reaction solution was adjusted to pH 8 with 1 mol / L sodium bicarbonate solution, and then precipitated with 500 ml of acetone for 24 hours. After filtration, the precipitate was dialyzed for 48 hours. Finally, the dialyzate was frozen and freeze-dried to obtain carboxylated methacryloyl polyvinyl alcohol (PGC). The synthesis process is as follows: Figure 1 shown.
[0061] The mass ratio of PVA to GMA is 1:0.0652, and the degree of substitution of the double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.01, which is recorded as low-substitution carboxylated methacryloyl polyvinyl alcohol, PGC-L. S2, preparation of dipotassium glycyrrhizinate phenylboronated; 4g of dipotassium glycyrrhizate was completely dissolved in 200ml of dimethyl sulfoxide (DMSO). 0.754g of N-hydroxysuccinimide (NHS), 1.254g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), and 1.43g of 3-aminophenylboronic acid were then added. The mixture was reacted at 30°C for 24h. The resulting solution was dialyzed for 72h. The dialyzate was then filtered and freeze-dried to obtain phenylboronated glycyrrhizic acid (GB).
[0062] The synthesis process of dipotassium glycyrrhizinate phenylboronate is as follows: Figure 2 shown.
[0063] The molar ratio of the carboxyl group on dipotassium glycyrrhizate to the amino group on 3-aminophenylboronic acid is 3:1.3.
[0064] S3. The carboxylated methacryloyl polyvinyl alcohol prepared in step S1 is dissolved in ultrapure water to prepare solution A (12% PGC-L) with a mass percentage concentration of 12% (m / v). The dipotassium glycyrrhizinate phenylborated prepared in step S2 is dissolved in ultrapure water to prepare solution B (8% GB) with a mass percentage concentration of 8% (m / v). Solution A and solution B (volume ratio of 1:1) are extruded and blended through a double-barreled syringe to obtain a rapidly moldable, strongly adhesive, highly stretchable, self-healing hydrogel.
[0065] See also Figure 3Shown are the NMR images of 3-aminophenylboronic acid (B), dipotassium glycyrrhizate (G), and dipotassium glycyrrhizinate phenylboronated (GB) in this example.
[0066] It can be seen from the NMR spectrum that the three strong peaks at 7~8 on GB belong to the hydrogen on the benzene ring of 3-aminophenylboronic acid, indicating that dipotassium phenylboronic acid glycyrrhizinate was successfully synthesized.
[0067] Figure 4 This is a diagram of the hydrogel self-healing process of Example 1.
[0068] First, the gel was cut into two parts and then fitted together. After 2 minutes of stretching, the gel did not break from the cut, indicating that the gel could self-heal within 2 minutes and had excellent self-healing properties.
[0069] Figure 5 This is a test diagram of the tensile properties of the hydrogel in Example 1.
[0070] It can be seen that the hydrogel can be stretched from the initial 4 cm to 30 cm without breaking, indicating that it has good tensile properties.
[0071] Figure 6 This is a test diagram of the adhesion performance of the hydrogel in Example 1.
[0072] It can be seen that the hydrogel can adhere well to different substrates, including glass, plastic, rubber, cardboard, and weights.
[0073] Examples 2-4 and Comparative Example 1 Examples 2-4 and Comparative Example 1 provide a method for preparing a hydrogel. Compared with Example 1, the difference is that in step S3, the concentrations of solution A and solution B are changed; the details are shown in Table 2; the rest are roughly the same as Example 1 and are not repeated here.
[0074] Example 5 Example 5 provides a method for preparing a hydrogel. Compared with Example 1, the difference is that 0.5 g of GMA is used in step S1, the mass ratio of PVA to GMA is 1:0.1, and the degree of substitution of the double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.02, which is recorded as high-substitution carboxylated methacryloyl polyvinyl alcohol, PGC-H; the rest is roughly the same as Example 1 and will not be repeated here.
[0075] Table 2 Experiments show that when the mass volume fraction of solution A (carboxylated methacryloyl polyvinyl alcohol aqueous solution) is less than 10%, the resulting hydrogel is poorly formed and easily collapses after demolding.
[0076] When the mass volume fraction of solution A is greater than 12%, the gelation speed is too fast and the solution is gelled before the double tubes are completely squeezed out, making it unworkable.
[0077] When the mass volume fraction of solution B (dipotassium glycyrrhizinate aqueous solution) is less than 6%, the ratio of the storage modulus to the loss modulus of the resulting hydrogel is close to 1. The performance of the formed gel is too poor to be tested on the machine.
[0078] When the mass volume fraction of solution A is greater than 10%, it can form a relatively stable gel when mixed with 6%~10% solution B. The resulting gel has a wide range of modulus distribution depending on the concentration of solution B.
[0079] See also Figure 7 Shown is the rheological properties-gel time diagram of the hydrogels of Examples 1-3, 5 and Comparative Example 1.
[0080] As can be seen in Example 1, when 8% GB and low-substituted PGC (PGC-L) were blended, a gel point appeared at 2 s, indicating a sol-gel transition. In contrast, in Comparative Example 1, when 4% GB and low-substituted PGC were blended, a gel point (sol-gel transition time) was required of 52 s. Furthermore, the gel point (sol-gel transition time) could not be detected for the highly substituted PGC (Example 4) and even higher GB concentration (Example 3) due to their rapid gelation.
[0081] In summary, gels with different concentration ratios can all form gels within 1 minute, and the moduli of gels obtained with different concentration ratios are also different.
[0082] The gel modulus formed by 4% GB is the lowest and G' and G" are relatively close, indicating that the formed gel is relatively soft and is near the junction point of sol-gel transition, indicating that the formed gel is unstable and not conducive to practical application.
[0083] When the concentration of PGC is fixed, the modulus of the gel formed gradually increases with the increase of GB solution concentration. When the concentration of GB is fixed, the modulus of the gel formed gradually increases with the increase of PGC substitution degree. In Example 5, when 8% GB and high-substitution PGC (PGC-H) form a gel, the modulus can reach 10 3 It is shown that the modulus of the prepared hydrogel can be controlled by controlling the concentration of GB and PGC.
[0084] See also Figure 8 Shown are the rheological properties-shear thinning diagrams of the hydrogels of Examples 1-3, 5 and Comparative Example 1.
[0085] It can be seen that the viscosity of the prepared hydrogel decreases with the increase of shear rate, and it is injectable.
[0086] Rheological properties - oscillatory strain of the hydrogels of Test Examples 1-3, 5 and Comparative Example 1. The results are shown in Table 3 and Figure 9 as follows.
[0087] Table 3 Please refer to Figure 9 as shown, which is the rheological property - oscillatory strain diagram of the hydrogels of Examples 1-3, 5 and Comparative Example 1. It can be seen that the maximum strains that hydrogels with different concentration ratios can withstand are different, and the hydrogel can withstand a maximum strain of 3000%.
[0088] Testing the rheological properties - alternating strain of the hydrogel: Dynamic self-healing test method: Amplitude scanning was performed at 1 Hz within the strain range of 0.1-10000% to determine the fracture strain of the hydrogel. Subsequently, an alternating step strain test was carried out to measure the modulus at a constant frequency of 1 Hz. The alternating strain was between 1% and 3000%, and the large strain and small strain alternated for 2 seconds and 60 seconds.
[0089] Please refer to Figure 10 as shown, which is the rheological property - alternating strain diagram of the hydrogels of Examples 1-2, 5 and Comparative Example 1.It can be seen that the hydrogels prepared from low-substitution PGC (PGC-L) and GB with different concentration ratios can withstand 90% compression and the compressive strength can reach 260kPa, while the high-substitution PGC breaks at 64%.
[0095] Comparative Example 2 Comparative Example 2 provides a method for preparing a hydrogel. Compared with Example 1, the difference is that in step S2, ultrapure water is used instead of dimethyl sulfoxide, that is, glycyrrhizic acid is modified under aqueous conditions. The rest is roughly the same as Example 1 and will not be repeated here.
[0096] Experiments show that under aqueous conditions, no matter how the ratio of phenylboronic acid to dipotassium glycyrrhizate or the pH value of the solution is controlled, aminophenylboronic acid cannot be successfully grafted, that is, phenylboronated dipotassium glycyrrhizate cannot be obtained.
[0097] Comparative Examples 3-4 Comparative Example 3-4 provides a method for preparing a hydrogel. Compared with Example 1, the difference is that in step S1, the pH of the reaction solution is changed, as shown in Table 4; the rest is roughly the same as Example 1 and will not be repeated here.
[0098] Table 4 As shown in Table 4, when the pH of the reaction solution is less than 7, carboxylated methacryloylated polyvinyl alcohol cannot be obtained. When the pH is greater than 9, the gel formed by mixing the obtained carboxylated methacryloylated polyvinyl alcohol with dipotassium glycyrrhizinate by phenylboration has poor performance.
[0099] The hydrogels prepared in Examples 1-5 were tested for tensile strain, gel time, and self-healing properties. The results are shown in Table 5.
[0100] Table 5 As shown in Table 5, the gel obtained in Example 1 has the best tensile properties and the fastest gelation speed. At the same time, the tensile strain and storage modulus of the hydrogels of Examples 1-5 have a wide distribution range, and the adhesion strength can reach more than 20 kPa. They can all achieve rapid gelation and can heal within 30 minutes.
[0101] The gel of Comparative Example 1 was poorly formed and collapsed after demoulding, and could not be put on the machine for mechanical property testing. Its gel time was 52 seconds.
[0102] The gel obtained in Comparative Example 4 was too brittle and had poor mechanical properties. Compared with the examples, its gel time was also longer.
[0103] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a rapidly moldable, strongly adhesive, and highly stretchable self-healing hydrogel, characterized in that: The following steps are involved: S1, preparation of carboxylated methacryloyl polyvinyl alcohol: polyvinyl alcohol is completely dissolved in a reaction vessel containing an organic solvent, followed by addition of a catalyst; thereafter, a glycidyl methacrylate solution is added, reacted for 5-10 hours, and then a succinic anhydride solution is added, and the reaction is continued for 5-10 hours. After completion of the reaction, the pH of the reaction solution is adjusted to 7-9; the solution is then precipitated with acetone, filtered, and dialyzed for 48-72 hours. Finally, the dialyzate is frozen and freeze-dried to obtain the carboxylated methacryloyl polyvinyl alcohol; S2, preparation of dipotassium glycyrrhizinate with phenylboronate: dipotassium glycyrrhizinate is completely dissolved in dimethyl sulfoxide, followed by addition of N-hydroxysuccinimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and 3-aminophenylboronic acid, and the mixture is reacted at 25-35°C for 20-48 hours; the reaction solution is then dialyzed for 48-72 hours, and the dialyzate is filtered and freeze-dried to obtain dipotassium glycyrrhizinate with phenylboronate; S3, the carboxylated methacryloyl polyvinyl alcohol prepared in step S1 is prepared into a solution A with a concentration of 10% to 12%, and the phenylborated dipotassium glycyrrhizate prepared in step S2 is prepared into a solution B with a concentration of 6% to 10%, and solution A and solution B are extruded and blended through a double-barreled syringe to obtain a self-healing hydrogel with strong adhesion and high stretchability that can be rapidly formed.
2. The method for preparing a rapidly prototyping, strongly adhesive, and highly stretchable self-healing hydrogel according to claim 1, wherein: In step S1, the mass ratio of polyvinyl alcohol to glycidyl methacrylate is 1:(0.064-0.1).
3. The method for preparing a rapidly prototyping, strongly adhesive, and highly stretchable self-healing hydrogel according to claim 2, wherein: When the mass ratio of the polyvinyl alcohol to glycidyl methacrylate is 1:(0.064-0.0652), the degree of substitution of double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.007-0.01; when the mass ratio of the polyvinyl alcohol to glycidyl methacrylate is 1:(0.096-0.1), the degree of substitution of double bonds of the obtained carboxylated methacryloyl polyvinyl alcohol is 0.018-0.
021.
4. The method for preparing a rapidly prototyping, strongly adhesive, and highly stretchable self-healing hydrogel according to claim 1, wherein: In step S2, the molar ratio of the carboxyl group on dipotassium glycyrrhizate to the amino group on 3-aminophenylboronic acid is 3:(1.25-1.3).
5. The method for preparing a rapidly prototyping, strongly adhesive, and highly stretchable self-healing hydrogel according to claim 1, wherein: In step S1, the mass ratio of succinic anhydride to polyvinyl alcohol is (1-4):
10.
6. The method for preparing a rapidly prototyping, strongly adhesive, and highly stretchable self-healing hydrogel according to claim 1, wherein: In step S1, the organic solvent is one of dimethyl sulfoxide, DMF, and chloroform.
7. The method for preparing a rapidly prototyping, strongly adhesive, and highly stretchable self-healing hydrogel according to claim 1, wherein: In step S1, the catalyst is p-dimethylaminopyridine, and the mass ratio of p-dimethylaminopyridine to polyvinyl alcohol is (0.1-0.15):
5.
8. The method for preparing a rapidly prototyping, strongly adhesive, and highly stretchable self-healing hydrogel according to claim 1, wherein: In step S1 , the pH of the solution is adjusted by dropwise adding sodium bicarbonate solution to the reaction system.
9. A rapidly moldable, strong-adhesive, highly stretchable, self-healing hydrogel, characterized in that: Prepared according to the preparation method according to any one of claims 1-8; the rapidly prototyping strong adhesion and high stretchability self-healing hydrogel has an adhesion strength of 20~65kPa and a tensile strain of 300~1050%.
Citation Information
Patent Citations
Injectable natural triterpene compound antibacterial hydrogel and preparation method thereof
CN110585122A
Medical hydrogel with pH sensitivity, self-healing nature and cell adhesion and preparation method thereof
CN108530651A
PVA supramolecular hydrogel and preparation method and application thereof
CN109575315A
Eight-arm polyethylene glycol-phenylboronic acid-glycyrrhizic acid drug delivery system with ROS intelligent response and preparation method of eight-arm polyethylene glycol-phenylboronic acid-glycyrrhizic acid drug delivery system
CN114146185A
Phenylboronic acid functionalized molybdenum disulfide quantum dot as well as preparation method and application thereof
CN115651631A